ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN PAI BERBASIS VIDEO - Renaldy Karsubi; Rendy Adrian (LPPM Universitas Bina Bangsa, 2024)
In learning at school, various media are definitely needed in order to improve the learning process. In this learning media there are various variations, for example using Learning Video media. It is hoped that this research can develop media needs in PAI subjects at SMPN 2 MANUHING. This type of research is development (R&D) with the ADDIE model. With research subjects totaling 20 respondents, the object of this research itself is an analysis of teacher needs in developing video-based learning media. In this research, the data collection technique/method is using a questionnaire for the Analysis of Needs for Development of PAI Media at SMPN 2 MANUHING in the form of a Google form which is distributed to students, especially in class IX, who have gone through several materials in PAI subjects at SMPN 2 MANUHING. Then the data was obtained from 30% of students who had difficulty in learning PAI and 65% of students who liked PAI subjects, while for this media data was obtained from 60% of students who needed Laptop/Computer Media in learning and 95% of students who agreed to use Video Media in learning PIE. From this data, it can be concluded that students at SMPN 2 MANUHING on average like PAI learning subjects but they lack media in learning, so by conducting this research it is hoped that media development in PAI learning at SMPN 2 MANUHING will be carried out